1991
DOI: 10.1080/10408399109527557
|View full text |Cite
|
Sign up to set email alerts
|

The influence of food on food intake: Methodological problems and mechanisms of action

Abstract: Emphasis has been placed on the understanding of the regulation of food intake in the hope of aiding the battle against obesity and of helping to ameliorate the anorexia of cancer and eating disorders. Available data suggest that the regulatory system is multifaceted and complex. This review focuses on current research on the regulation of appetite and satiety by carbohydrates, fats, and proteins as well as by artificial sweeteners. Some methodological problems and potential mechanisms of action at the biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 175 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…It should be noted that greater fat content of food can delay gastric emptying and thus affect food appetite (Hunt, 1980;Roehrig, 1991). Pilot work with this animal model of tumor-induced anorexia indicated that changes in gastric emptying do not occur with progressive tumor growth (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…It should be noted that greater fat content of food can delay gastric emptying and thus affect food appetite (Hunt, 1980;Roehrig, 1991). Pilot work with this animal model of tumor-induced anorexia indicated that changes in gastric emptying do not occur with progressive tumor growth (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 88%